2012
DOI: 10.1016/j.cell.2012.10.041
|View full text |Cite
|
Sign up to set email alerts
|

TMHS Is an Integral Component of the Mechanotransduction Machinery of Cochlear Hair Cells

Abstract: SUMMARY Hair cells are mechanosensors for the perception of sound, acceleration and fluid motion. Mechanotransduction channels in hair cells are gated by tip links, which connect the stereocilia of a hair cell in the direction of their mechanical sensitivity. The molecular constituents of the mechanotransduction channels of hair cells are not known. Here we show that mechanotransduction is impaired in mice lacking the tetraspan TMHS. TMHS binds to the tip-link component PCDH15 and regulates tip-link assembly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
400
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(453 citation statements)
references
References 54 publications
38
400
3
Order By: Relevance
“…In mice, mutations or deletions of Lhfpl5, Myo7a, and Ush1c cause the reduction or mislocalization of PCDH15 in stereocilia (Senften et al, 2006;Yan et al, 2011;Xiong et al, 2012). In agreement with previous findings, we observed that Pcdh15-CD3-EGFP is absent at the tips of mature hair bundles in lhfpl5a, myo7aa, and cdh23 mutant fish.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In mice, mutations or deletions of Lhfpl5, Myo7a, and Ush1c cause the reduction or mislocalization of PCDH15 in stereocilia (Senften et al, 2006;Yan et al, 2011;Xiong et al, 2012). In agreement with previous findings, we observed that Pcdh15-CD3-EGFP is absent at the tips of mature hair bundles in lhfpl5a, myo7aa, and cdh23 mutant fish.…”
Section: Discussionsupporting
confidence: 82%
“…The cytoplasmic tail of PCDH15 has been shown to interact in vitro or in heterologous experiments with a number of proteins implicated in mechanotransduction, including LHFPL5, MYO7A, and a PDZ-containing protein, USH1C (also known as Harmonin) (El-Amraoui and Petit, 2005;Yan and Liu, 2010;Xiong et al, 2012). In mice, mutations or deletions of Lhfpl5, Myo7a, and Ush1c cause the reduction or mislocalization of PCDH15 in stereocilia (Senften et al, 2006;Yan et al, 2011;Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LHFPL5 protein is an integral component of the mechanotransduction machinery in both OHCs and IHCs, and its absence leads to early hair cell degeneration, profound deafness, and severe vestibular dysfunction. 18 Because this model is on the C57BL/6 background and our previous gene transfer experiments were performed on CD1 mice, we tested whether exo-AAV transduces hair cells with the same efficiency on the C57BL/6 background. We did not observe any differences between CD1 and C57BL/6 transduction rates using exo-AAV1-GFP ( Figure S5).…”
Section: Exo-aav Outperforms Conventional Aav In Transgene Delivery Tmentioning
confidence: 99%
“…These proteins form multimolecular complexes creating an intricate network in which signaling molecules complex together giving origin to subcellular structures known as the tetraspan-enriched microdomains. Thus, by integrating different signaling pathway components, these small transmembrane proteins act as modulators of the signaling cascade and, ultimately, of cell homeostasis (Adato et al, 2002;Charrin et al, 2003;Chen et al, 2003;Xiong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%